2015
DOI: 10.1021/acs.analchem.5b00335
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Colorimetric Detection of 17β-Estradiol: The Effect of Shortening DNA Aptamer Sequences

Abstract: We report a strategy enabling ultrasensitive colorimetric detection of 17β-estradiol (E2) in water and urine samples using DNA aptamer-coated gold nanoparticles (AuNPs). Starting from an established sensor format where aggregation is triggered when target-bound aptamers dissociate from AuNP surfaces, we demonstrated that step-change improvements are easily accessible through deletion of excess flanking nucleotides from aptamer sequences. After evaluating the lowest energy two-dimensional configuration of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
186
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(197 citation statements)
references
References 39 publications
9
186
2
Order By: Relevance
“…Previous research has demonstrated the extraordinary potential of sensor devices constructed from aptamers, single‐stranded DNA or RNA molecules attached to nanoparticles or nanotubes . These “aptasensors” combine the unique optical and electrical properties of the nanomaterials with the ability of aptamers to bind with high affinity and specificity to predefined targets .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated the extraordinary potential of sensor devices constructed from aptamers, single‐stranded DNA or RNA molecules attached to nanoparticles or nanotubes . These “aptasensors” combine the unique optical and electrical properties of the nanomaterials with the ability of aptamers to bind with high affinity and specificity to predefined targets .…”
Section: Introductionmentioning
confidence: 99%
“…2,4 However, this approach was restricted to a limited range of target proteins, and device fabrication and operation was subject to tight constraints to maintain antibody stability. [15][16][17] These short strands of DNA can be generated via a synthetic evolution process to bind with specificity for different types of targets, including cells, 18 proteins, 15,[19][20][21] molecules, [22][23][24][25] and even ions. 11,12 The emergence of synthetic receptors such as DNA aptamers 13,14 has stimulated new opportunities for CNT biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…Mirkin’s group first reported the unique optical properties of an aggregate of GNPs, which induces interparticle plasmon coupling, resulting in a redshift in the LSPR spectrum21222324. The GNP aggregation causes a LSPR shift that is manifested as a useful spectrum-based biosensing platform1429. Meanwhile, it belongs to a homogeneous binding assay, which is carried out in solution without sophisticated processes, such as separation, immobilization, or washing steps.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used method for spectral analysis in chemistry and biology is the measurement of a spectral peak position or a corresponding intensity value12131415. As with any traditional spectrometer, performance is highly affected by the spectral resolution.…”
mentioning
confidence: 99%